Mengedukasikan Masyarakat Sekitar Sungai Deli Medan Mengenai Dampak Sungai Yang Tidak Bersih - Reniwati Lubis; Herri Trisna Fianto; Fitri Evita; Syafriyandi; Dewantoro Lase; Ika Agustina (Unity Academy, 2022)
It is not surprising to see the current state of the city of Medan. Every time it rains the streets are always filled with floods. The government has made water canals on every side of the road so that the water that is on the road goes straight to the channel. However, the program created by the government has not been implemented properly because the waterways are full of garbage. These waterways are directly connected to the Deli Medan river. Not only that, the people who live around the Deli Medan river often throw their waste into the Deli Medan river. The purpose of this community service is so that the people living around the Deli Medan river are aware of the impacts or dangers of an unclean river. This community service method is carried out in three stages, namely: the preparatory stage, the implementation stage and the closing stage. At this preparatory stage it is necessary to coordinate with partners, and at the implementation stage the community service team with PDRI SUMUT partners and the Medan BPBD go directly to the location to provide education to the people who live around the Deli Medan river which will have an impact on the river which is not clean by using canoes or boats from the Medan BPBD along the Deli Medan river. In the final stage evaluation and reporting is carried out. The result of this community service is that it is hoped that the people living around the Deli Medan river will understand the damage or danger of an unclean river.